Analisis Literasi Teknologi Informasi Guru Matematika SMK Swasta Jakarta Selatan Ditinjau dari Aspek Manajemen Pendidikan - Huri Suhendri; Mailizar Mailizar; Rita Ningsih; Rita Retnowati (Tadbir : Jurnal Studi Manajemen Pendidikan, 2020)
In the era of information technology-based 4.0, all fields use information technology, as well as in the world of education. In learning, the use and use of information technology is very important in supporting the smooth teaching and learning process. So that the ability of teachers in information technology literacy is very important and needs to be developed. This study aims to describe the level of information technology literacy of mathematics teachers in private vocational schools in South Jakarta and identify the factors that influence it. The research method used is descriptive qualitative method. The research sample was 41 mathematics teachers at private vocational schools in South Jakarta, who were taken by purposive sampling technique. Information techniques through questionnaires and interviews. The results showed that the level of information technology literacy for mathematics teachers in private vocational schools in South Jakarta was still low. One of the factors affecting literacy is the lack of training in the use of information.